2021
DOI: 10.1055/s-0041-1730027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Sepsis Alert in the Pediatric Acute Care Setting

Abstract: Background Severe sepsis can cause significant morbidity and mortality in pediatric patients. Early recognition and treatment are vital to improving patient outcomes. Objective The study aimed to evaluate the impact of a best practice alert in improving recognition of sepsis and timely treatment to improve mortality in the pediatric acute care setting. Methods A multidisciplinary team adapted a sepsis alert from the emergency room setting to facilitate identification of sepsis in acute care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…It is likely that the timely improvement in initial sepsis management with fluid and antibiotics, which was mediated by the sepsis EAS implementation, was associated with a reduction in mortality and LOS in PICU in our study. Similar findings were reported in a pediatric acute care setting where an analysis of the pre- and post-EAS implementation groups showed a reduction in both the 3-day sepsis-attributable mortality (2.53 vs. 0%] and 30-day mortality (3.8 vs. 1.3%) 30 . In adults, similar improvements in mortality and LOS outcomes have been associated with an EAS integrated with a multifaceted identification and intervention approach 3 , 15 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It is likely that the timely improvement in initial sepsis management with fluid and antibiotics, which was mediated by the sepsis EAS implementation, was associated with a reduction in mortality and LOS in PICU in our study. Similar findings were reported in a pediatric acute care setting where an analysis of the pre- and post-EAS implementation groups showed a reduction in both the 3-day sepsis-attributable mortality (2.53 vs. 0%] and 30-day mortality (3.8 vs. 1.3%) 30 . In adults, similar improvements in mortality and LOS outcomes have been associated with an EAS integrated with a multifaceted identification and intervention approach 3 , 15 .…”
Section: Discussionsupporting
confidence: 84%
“…The need for automated, effective, and timely screening tools for sepsis screening triggered further investment and investigations aimed at integrating health informatics and data analysis models 23,24 . The growing interest in machine learning and big data analysis fueled this innovative approach, which resulted in the development of automated decisions-aiding models and electronic alerts for potential sepsis cases 3,13,23,[25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] Research evaluating the effect of CDSS on provider practices have had mixed findings. [26][27][28][29][30][31][32][33][34][35][36][37][38][39] Studies on CDSS tools have shown interventions both successfully changing provider behavior 26,27,[30][31][32][35][36][37][38][39] and having no impact on provider practice. 28,34 Previous research reported high levels of interest in PrEP-specific CDSS support among PrEP-inexperienced providers and found that a CDSS would have the greatest impact on knowledge and practice among providers without PrEP experience.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(2) Diagnostic criteria The diagnostic criteria for the TCM evidence of sepsis [7][8] are shown in Table 1.…”
Section: Study Populationmentioning
confidence: 99%